Concept Of Educational Social Contact In Family, School and Community - Muhammad Bustomi; Abdullah Idi; Karoma (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2024)
Educational social contact is a form of interaction that supports the learning process and character building of individuals, both in the family, school and community environments. This article aims to explore and elaborate the concept and important role of educative social contact in three main domains, namely family, school and community. Using a qualitative method based on a literature study, this research identifies and analyzes the various forms and impacts of educational interactions that occur in these environments. The results of the analysis show that educative social contacts that occur in families, schools and communities play a very important role in the formation of individuals' character, social skills and moral values. Family interactions, such as modeling, educative communication and character education, form the basis of child development. Schools as social agents develop students' academics and character through formal, non-formal learning and social interactions. Society introduces social norms, diversity, and the importance of cooperation and empathy. Participation in social activities, multicultural interactions and use of public facilities help individuals develop social skills to contribute to community life. These three environments complement each other in shaping individuals who are intelligent, good character and adaptive.